Recombinogenic effects of suppressors of position-effect variegation in Drosophila. - Westphal, T.; Reuter, G. (Genetics, 2002)
Compact chromatin structure, induction of gene silencing in position-effect variegation (PEV), and crossing-over suppression are typical features of heterochromatin. To identify genes affecting crossing-over suppression by heterochromatin we tested PEV suppressor mutations for their effects on crossing over in pericentromeric regions of Drosophila autosomes. From the 46 mutations (28 loci) studied, 16 Su(var) mutations of the nine genes Su(var)2-1, Su(var)2-2, Su(var)2-5, Su(var)2-10, Su(var)2-14, Su(var)2-15, Su(var)3-3, Su(var)3-7, and Su(var)3-9 significantly increase in heterozygotes or by additive effects in double and triple heterozygotes crossing over in the ri-p(p) region of chromosome 3. Su(var)2-2(01) and Su(var)2-14(01) display the strongest recombinogenic effects and were also shown to enhance recombination within the light-rolled heterochromatic region of chromosome 2. The dominant recombinogenic effects of Su(var) mutations are most pronounced in proximal euchromatin and are accompanied with significant reduction of meiotic nondisjunction. Our data suggest that crossing-over suppression by heterochromatin is controlled at chromatin structure as well as illustrate the possible effects of heterochromatin on total crossing-over frequencies in the genome.